Study of the Use of Fiber Hinges in Non-linear Static Analysis - Kurniawandy, Alex; Yaren, Rezha; Nugraha, Rendi Adi; Jamil, Hafizd Ahmed (Journal of Infrastructure and Construction Technology, 2023)
Pushover analysis as known as non-linear static analysis is one of the structural analysis procedures that is widely used in seismic assessment and performance evaluation of existing structures . In the nonlinear analysis procedure, the behavior of the structure due to external loads acting can be seen from the status of the joints formed. One of the joint models that is less commonly used in non-linear static analysis is the fiber hinge joint modeling. Fiber hinge is a nonlinear joint model that can consider distributed plasticity along with its structural elements. Study this learn possibility difference in results analysis use fiber hinge because properties component specified nonlinear _ researcher . In order to study the impact of the use of joint modeling variations in nonlinear analysis, a regular reinforced concrete structure model with 4 height variations namely 3, 4, 5, and 6 floors which were analyzed with two different types of joint modeling. Fiber hinges and conventional lumped hinges will be defined in the cross section. Research results show that the use of fiber hinge in each model produces score relative moment _ small however given rotation _ relatively more big than lumped hinge as well relative base shear value small than lumped hinges. Considering the fiber hinge is method that gives state of natural response so that deformation globally generated _ more big than lumped hinges. This thing take effect to determination structure performance value.